If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 15 = -3x + -11 Reorder the terms: 15 + 5x = -3x + -11 Reorder the terms: 15 + 5x = -11 + -3x Solving 15 + 5x = -11 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 15 + 5x + 3x = -11 + -3x + 3x Combine like terms: 5x + 3x = 8x 15 + 8x = -11 + -3x + 3x Combine like terms: -3x + 3x = 0 15 + 8x = -11 + 0 15 + 8x = -11 Add '-15' to each side of the equation. 15 + -15 + 8x = -11 + -15 Combine like terms: 15 + -15 = 0 0 + 8x = -11 + -15 8x = -11 + -15 Combine like terms: -11 + -15 = -26 8x = -26 Divide each side by '8'. x = -3.25 Simplifying x = -3.25
| x=5x^2+x*5 | | N+.6=n+.1+2n | | s^2+3s+8s+24= | | (1/6)^5 | | x^2+3x+24=47 | | 0=5x^2-24x+37 | | 4y+(y-1)=29 | | 4y-y+1=13 | | 5x^2+3x+24=47 | | 20=m+1 | | (2y+3)-4=9 | | k=1.6d+300 | | 3q=18 | | 10z=9z-11 | | 41=5w-9 | | a+2(a-3)=15 | | 4+4x=-24 | | -6+2*y=0 | | j+6=9 | | 7x-15=4x-6 | | -2+2*y=0 | | 6=2p | | 2u-7=-19 | | 6+2*y=0 | | 173-w=224 | | 6(y-3)=6y+7 | | n/9=16/24 | | -11=4v+5 | | 4x^2-49+12=0 | | 4v-15=45 | | -5x=3y | | -6-2y=0 |